THE EFFECTIVENESS OF DIGITAL MEDIA IN FACILITATING THE UNDERSTANDING OF ISLAM FOR THE Z-GENERATION IN THE ERA OF DISRUPTION - Eri Murniasih; B. Syafuri; Wasehudin Wasehudin (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2024)
The era of disruption is marked by rapid technological developments that change various aspects of life, including how to obtain information and knowledge. Generation Z, as a generation that grew up in a digital environment, has extensive access to various digital media that can be used to deepen their understanding of the Islamic religion. This article explores multiple digital platforms that provide educational content about Islam. Through literature studies and case analysis with a qualitative approach, this article highlights the benefits and challenges of using digital media in religious education. Data was collected from various literature sources and interviews with Generation Z, namely the Informatics Engineering Study Program students at Serang Raya University. The research results show that Generation Z prefers to use digital media to increase and improve their religious knowledge rather than conventional media because it is more effective, efficient, and accessible anytime, anywhere, according to Generation Z's preferences and learning styles. However, challenges such as the validity of the information and interference from irrelevant content are also identified. This article concludes that with the right strategy, good digital literacy, and continued guidance from teachers, educators, and religious leaders, digital media has great potential to become an effective tool in facilitating Generation Z's understanding and interest in Islamic teachings and can help them practice religious teachings better.